Ancient DNA From Museum Specimens and Next Generation Sequencing Help Resolve the Controversial Evolutionary History of the Critically Endangered Puebla Deer Mouse - Castañeda-Rico, Susette; León-Paniagua, Livia; Edwards, Cody W.; Maldonado, Jesús E. (Frontiers in Ecology and Evolution, 2020)
Key insights into the evolutionary history of recently extinct or critically endangered species can be obtained through analysis of genomic data collected using high-throughput sequencing and ancient DNA from museum specimens, particularly where specimens are rare. For instance, the evolutionary history of the critically endangered Puebla deer mouse, Peromyscus mekisturus, remains unclear due to discordance between morphological and molecular phylogenetic analyses. However, previous molecular analyses were based on PCR and Sanger sequencing of only a few mitochondrial genes. Here, we used ancient DNA from historical museum specimens followed by target enrichment and high-throughput sequencing of several thousand nuclear ultraconserved elements and whole mitochondrial genomes to test the validity of the previous phylogenetic placement of P. mekisturus. Based on UCEs and mitogenomes, our results revealed that P. mekisturus forms a well-supported distinct lineage outside the clade containing all other members of the Peromyscus melanophrys group. Additionally, the mitogenome phylogeny further supports the placement of P. mekisturus as the sister species of the genus Reithrodontomys. This conflicts with the previous mtDNA phylogenetic reconstruction, in which P. mekisturus was nested within the species P. melanophrys. Our study demonstrates that high-throughput sequencing of ancient DNA, appropriately controlling for contamination and degradation, can provide a robust resolution of the evolutionary history and taxonomic status of species for which few or no modern genetic samples exist. In light of our results and pending further analysis with denser taxon sampling and the addition of morphological data, a re-evaluation of the taxonomy and conservation management plans of P. mekisturus is needed to ensure that the evolutionary distinctiveness of this species is recognized in future conservation efforts.